Stigma and Take-up of Labor Market Assistance: Evidence from Two Field Experiments - Adam Osman; Jamin D. Speer (Institute of Labor Economics (IZA), 2023)
Aversion to "stigma" - disutility associated with a program or activity due to beliefs about how it is perceived - may affect labor market choices and utilization of social programs, but empirical evidence of its importance is scarce. Using two randomized field experiments, we show that stigma can affect consequential labor market decisions. Treatments designed to alleviate stigma concerns about taking entry-level jobs - such as how those jobs are perceived by society - had small average effects on take-up of job assistance programs. However, using compositional analysis and machine learning methods, we document large heterogeneity in the responses to our treatments. Stigma significantly affects the composition of who takes up a program: the treatments were successful in overcoming stigma for older, wealthier, and working respondents. For other people, we show that our treatments merely increased the salience of the stigma without dispelling it. We conclude that social image concerns affect labor market decisions and that messaging surrounding programs can have important effects on program take-up and composition.
Keywords: J22; C93; I38; Z13; 330; stigma; experiment; machine learning